Equine in Vitro Digestibility Using Different Cecal Fluid Dilutions. (7th May 2021) - Davis, Cody; Carrell, Russell C; Thompson, Serena; Cole, Madison; Dillard, S Leanne L
Abstract: In vitro digestibility (IVTD) is a useful tool for determining nutritive value of forages. The majority of equine forage digestion occurs in the cecum; however, many studies use fecal inoculum. The current study aimed to determine the optimal buffer:cecal fluid for batch culture fermentation and compare this method with fecal IVTD. Three horses were sourced from the Auburn University Veterinary School. Fecal material was collected via a rectal grab sample, placed in a plastic bag, and into a 39°C water bath. The cecal contents were collected using an abdominal incision within 5 min of termination. Contents were placed in a pre-warmed (39°C) thermos. Cecal fluid was strained and proportioned into 3 treatments (100:0, 75:25, and 50:50 cecal fluid:buffer). Fecal material was weighed and mixed with buffer to achieve a 10:90 by weight. Three samples of alfalfa, bermudagrass, and perennial peanut hay were randomly assigned to a fluid treatment and placed in the respective jar, digested for 48h, then underwent neutral detergent fiber analysis. The experiment was designed as a 4 × 3 factorial with horse considered random (n = 9). Statistical analysis was conducted using Proc Mixed (SAS Inst, Cary, NC) with α = 0.05. There was no effect of fluid treatment on IVTD (P = 0.12). However, a forage effect was observed (P < 0.001). Alfalfa and perennial peanut IVTD were not different (75.6%; P = 0.40), but greater (P < 0.001) than bermudagrass (48.1%). This study showed that no difference in cecal fluid and fecal material occurred when used as microbial inoculant sources for a Daisy-II batch fermentation for determination of equine IVTD.